2014
DOI: 10.1371/journal.pone.0110026
|View full text |Cite
|
Sign up to set email alerts
|

A Beneficiary Role for Neuraminidase in Influenza Virus Penetration through the Respiratory Mucus

Abstract: Swine influenza virus (SIV) has a strong tropism for pig respiratory mucosa, which consists of a mucus layer, epithelium, basement membrane and lamina propria. Sialic acids present on the epithelial surface have long been considered to be determinants of influenza virus tropism. However, mucus which is also rich in sialic acids may serve as the first barrier of selection. It was investigated how influenza virus interacts with the mucus to infect epithelial cells. Two techniques were applied to track SIV H1N1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 50 publications
(52 reference statements)
4
98
1
2
Order By: Relevance
“…This is an important host defense mechanism, as pathogens trapped in mucus are expelled via mucociliary clearance before they are able to bind to cells and initiate an infection (27,29). The interaction between NA and mucins was hypothesized as early as 1943; more recently, by studying viral binding to MDCK cells, A549 cells, erythrocytes, and isolated respiratory mucus, NA activity has been shown to be important in initiating infection and viral penetration of mucus in vitro (18,20,(30)(31)(32). Mucus overlying frozen human trachea/bronchial tissue sections bound to viruses in a manner which appeared to be mediated by sialic acids (20).…”
Section: Discussionmentioning
confidence: 99%
“…This is an important host defense mechanism, as pathogens trapped in mucus are expelled via mucociliary clearance before they are able to bind to cells and initiate an infection (27,29). The interaction between NA and mucins was hypothesized as early as 1943; more recently, by studying viral binding to MDCK cells, A549 cells, erythrocytes, and isolated respiratory mucus, NA activity has been shown to be important in initiating infection and viral penetration of mucus in vitro (18,20,(30)(31)(32). Mucus overlying frozen human trachea/bronchial tissue sections bound to viruses in a manner which appeared to be mediated by sialic acids (20).…”
Section: Discussionmentioning
confidence: 99%
“…11 Others have shown that the influenza virus is immobilized in airway mucus through adhesive interactions of the virus with sialic acid on mucins found in the gel layer, as influenza requires the same specific binding to sialic acid on cell-surface glycans to mediate epithelial cell entry. 89 The influenza envelope contains a sialic-acid cleaving enzyme, neuraminidase, which was shown to facilitate its passage through the mucus gel layer. 89 Neutralizing antibodies against inhaled gene vectors can also impair penetration through the airway mucus gel layer.…”
Section: Trapping Mechanismsmentioning
confidence: 99%
“…89 The influenza envelope contains a sialic-acid cleaving enzyme, neuraminidase, which was shown to facilitate its passage through the mucus gel layer. 89 Neutralizing antibodies against inhaled gene vectors can also impair penetration through the airway mucus gel layer. Gene vectors coated with a sufficient number of antibodies are subject to multivalent adhesive trapping in mucus since the Fc region of antibodies binds, albeit with low affinity, to mucus.…”
Section: Trapping Mechanismsmentioning
confidence: 99%
“…Viral purification was performed as described by Yang et al (2014). Briefly, culture fluids of EHV-1-infected (03P37 and 97P70) RK-13 cells were clarified and virus was collected after centrifugation.…”
Section: Cell Viabilitymentioning
confidence: 99%